Job burnout among nurses in Senawang Indah Medical Centre Sdn Bhd (SALAM) / Shahirah Farhah Sharifuddin - Sharifuddin, Shahirah Farhah (Faculty of Business and Management, 2018)
Based on the study, in health profession, researcher can see that they are really faces job burnout especially among the staff nurses. Staff nurse are easily lead to job burnout since they have a lot of contact with big amount of patients in a day. The main aim and objective of this study is to identify the relationship between emotional exhaustion, depersonalization, and personal accomplishment with job burnout. This study intended to identify the causes that influence the job burnout among staff nurses in Senawang Indah Medical Centre Sdn Bhd (SALAM). Quantitative approach and qualitative approach are being used to gain information for this study. The staff nurse in this hospital as the respondent for this research. It is to learn more about what that lead they to job burnout since their job scope are very broad. The data collected for this study was obtained from the Human Resource Manager and nurse manager. The questionnaire that include in this study for the survey consists of six questionnaires which are socio-demographic questionnaire, job burnout, emotional exhaustion, depersonalization, and personal accomplishment. The research technique that researcher used to conduct this research is survey research. A survey is a list of questions aimed at extracting specific data from a staff nurse. Where it shows the result of personal accomplishment with job burnout among nurses in Senawang Indah Medical Centre Sdn Bhd (SALAM) have positively influences, which it is (p<0.05), make it as the highest positively relationships. The findings of the study showed that job burnout positively influences emotional exhaustion, which it is (p<0.05). while, the findings of the study showed that the job burnout among nurses in Senawang Indah Medical Centre Sdn Bhd (SALAM) negatively influences the working experience, which the significant more than 0.05.